BIP and the unfolded protein response are important for potyvirus and potexvirus infection. (1st November 2020) - Herath, Venura; Gayral, Mathieu; Miller, Rita K.; Verchot, Jeanmarie
ABSTRACT: Plant potexvirus and potyvirus infection can trigger endoplasmic reticulum (ER) stress. ER stress signaling increases the expression of cytoprotective ER-chaperones, especially the BiP chaperones which contribute to pro-survival functions when plants are subjected to infection. The inositol requiring enzyme (IRE1) is one ER stress sensor that is activated to splice the bZIP60 mRNA which produces a truncated transcription factor that activates gene expression in the nucleus. The IRE1/bZIP60 pathway is associated with restricting potyvirus and potexvirus infection. Recent data also identified the IRE1-independent UPR pathways led by bZIP28 and bZIP17 contribute to potexvirus and potyvirus infection. These three bZIP pathways recognize cis -regulatory elements in the BiP promoters to enhance gene expression. BiP is part of a negative feedback loop that regulates the activities of the ER stress transducers IRE1, bZIP28, and bZIP17 to block their activation. We discuss a model in which bZIP60 and bZIP17 synergistically induce BiP and other genes restricting Plantago asiatica mosaic virus (PlAMV; a potexvirus) infection while bZIP60 and bZIP28 independently induce genes supporting PlAMV infection. Regarding Turnip mosiac virus (TuMV, a potyvirus) infection, bZIP60 and bZIP28 serve to repress local and systemic infection. Finally, tauroursodeoxycholic acid treatments were used to demonstrate that the protein folding capacity significantly influences PlAMV accumulation.